REPREZENTAREA SOCIALĂ A FAMILIEI CONTEMPORANE ÎN REPUBLICA MOLDOVA - Daniela CAZACU (Psihologie, 2023)
The study was aimed at developing the theoretical foundations regarding the family and social representation, determining the content of the social representation of the family in the Republic of Moldova, determining the possibilities for the development of social representation by modeling some episodes of change in social practice applying a psychological intervention program. The study involved 663 randomly selected individuals aged 17 to 50. The psychological intervention program developed by us can serve as a basis for the development of other psychosocial intervention programs. In the same way, we believe that the results of the experimental investigation, the psychological intervention program will be useful for school psychologists, teaching staff and counseling psychologists, and the program can be proposed to teachers who teach civic education in middle and high school.